Penyuluhan Kesehatan Perilaku Hidup Bersih Dan Sehat (PHBS) Tatanan Rumah Tangga Desa Baji Minasa Kec. Gatarangkeke Kabupaten Bantaeng - Dewi Arisanti; Nurhidayat Nurhidayat; Mujahida Basarang (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2020)
Abtract Clean and Healthy Life Behavior (PHBS) is a step that must be taken to achieve optimal health for everyone. Healthy conditions do not necessarily occur, but must always be pursued from unhealthy to a healthy life and create a healthy environment. This effort must start from oneself and the household, this effort is to realize the highest degree of public health as an investment for the development of healthy and productive human resources. At present community awareness of health and understanding of clean and healthy lifestyles, especially in villages is still very low. For this reason, the provision of counseling related to clean and healthy living behaviors is expected to be an effort to make the community aware of the importance of making clean and healthy living behaviors in the household setting. The team made preparations for community service activities including the creation of banners, counseling materials to the community at the village office of Bajiminasa village on March 8, 2019. From these community service activities, it can be concluded that the community's knowledge and understanding of clean and healthy life behavior increased.